Factors and components of Social Media that Influence the Perceptions of Local Food Companies in China - Zheng, Yingying; Youngmee, Kotchaphan; Liamthaisong, Khachakrit (Journal of Ecohumanism, 2024)
To investigate and explore the impacts of social media on brand awareness and user engagement of local food enterprises in China and to identify key influencing factors and components through empirical analysis. Data were collected through questionnaire surveys: the 30-item Questionnaire on Leader-User Engagement Interaction Behavior (QLUEIB) on five scales including social media platform usage, content type, user interaction, data analysis, and the influence of opinion leaders on brand awareness, the factors influencing brand awareness formation was assessed in the 10-item Brand Awareness Attitude (BAA), and user engagement was analyzed in the 10-item User Engagement Attitude (UEA). Associations between the means five scales of the QLUEIB with the BAA and UEA attitudes were assessed. The QLUEIB, BAA, and UEA are valid and reliable. The R2 values indicate that 50% and 47% of the variance in personalities’ attitudes to their perceptions of their social media influence toward the local food companies in China was attributable to their brand awareness, and engagement factors’ components, correlatedly. Suggestions that, using media are put forward to optimize content strategies, enhance user interaction, make sense of data analysis, and strengthen brand management to indicate a full understanding of the role of social media in brand promotion.